Situación ocupacional del nutricionista-dietista: egresados de la Universidad Nacional, periodo 1973-1980 - Aura García Ulloa; Carmen E. de Petán (Revista de la Facultad de Medicina, 1986)
This study allowed to identify the occupational adjustment necessary for the replanning of the Nutrition and Dietetics Curriculum at the National University. The results reflect the general situation of the graduate's professional  performance and the main and secondary activities developed according to the established functions in the academic program. However, it was detected that the Nutritionist does not perform all expected activities owing to possible influencing factors related to curricuculum, environment or individual  characteristics of the professional. Although, the University offered a good preparation to the Nutritionist in the management of dietetic patients, in the assessment of nutritional status of the individual, in food service management, the professionals show interest in continuing education to reinforce their fundamental knowledge in: nutrition, physiology and biochemistry; physiopathology and diet therapy; microbiology and food handling; general administration and research methodology.